2014
DOI: 10.1002/jso.23784
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome after cytoreductive surgery and HIPEC for colorectal peritoneal carcinomatosis with signet ring cell histology

Abstract: Patients with SRCC and PC treated with CRS+HIPEC have a poor median survival only slightly reaching over 1 year. In the presence of other relative contraindications, SRCC histology should refrain a surgeon from performing CRS and HIPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 41 publications
3
33
1
Order By: Relevance
“…While no definite data regarding the specific outcome after CRS/HIPEC of those HG subgroups are available, it has been shown in prior studies that outcomes for intestinal and signet-ring adenocarcinomas are worse than for PMCA. [15][16][17] In contrast, in patients with LG appendicular neoplasms, we observed excellent long-term CSS and DFS. Although DPAM is normally not a rapidly progressing disease, patient morbidity still was high before the upcoming CRS/ HIPEC.…”
Section: Discussionmentioning
confidence: 92%
“…While no definite data regarding the specific outcome after CRS/HIPEC of those HG subgroups are available, it has been shown in prior studies that outcomes for intestinal and signet-ring adenocarcinomas are worse than for PMCA. [15][16][17] In contrast, in patients with LG appendicular neoplasms, we observed excellent long-term CSS and DFS. Although DPAM is normally not a rapidly progressing disease, patient morbidity still was high before the upcoming CRS/ HIPEC.…”
Section: Discussionmentioning
confidence: 92%
“…So authors concluded that CRS and HIPEC seems to be safe and beneficial in peritoneal metastases of colorectal origin[33]. But literature assessing benefit of HIPEC for SRCC is scarce and controversial with studies denying[34,35] and implying[36] benefit of HIPEC in this subgroup. But these reports are retrospective and are fraught with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…A macroscopic complete resection was achieved in 97.2% of cases. Recurrences occur in 68.8% of SRCC, and the median survival was 14.1 months, whereas the median survival in the adenocarcinoma group was 35.1 months (P < 0.01)[44]. The investigators claim that SRCC histology should refrain a surgeon from performing cytoreductive surgery and HIPEC.…”
mentioning
confidence: 99%